The Mechanism of Oxidation of Formic Acid in Acidic Solutions on Boron‐Doped Diamond Electrodes: A Quantum Chemical Study. Issue 11 (15th May 2019) - Ignaczak, Anna; Adamiak, Marta; Santos, Elizabeth; Schmickler, Wolfgang
Abstract: The oxidation of formic acid (syn‐FA and anti‐FA forms) by hydroxyl radicals generated on the boron‐doped diamond anode in acidic aqueous solution is examined by means of quantum chemical calculations under the assumption that the reaction proceeds according to the outer sphere mechanism, without adsorption of reactants on the electrode. A number of possible reactive complexes [FA ⋅⋅⋅ HO] and product complexes [COOH ⋅⋅⋅ H2 O] formed in solution, as well as the corresponding transition‐state structures, were optimized at the MP2/aug‐cc‐pVTZ theory level, followed by single‐point CCSD(T) calculations. It is shown that in aqueous solution the formyl hydrogen abstraction is energetically favored and associated with the effective barriers Δ H b of 0.1–0.2 eV, which are about two times lower than that for carboxylic hydrogen abstraction. The overall reaction is highly exothermic (Δ H of about −5.8 eV) and expected to be very fast. The results confirm the validity of our hypothesis that the electrochemical incineration of formic acid may occur in solution according to the outer sphere mechanism. Abstract : It all checks out : Based on the results of quantum calculations, the mechanism of oxidation of formic acid by hydroxyl radicals electrogenerated on the boron‐doped diamond anode is presented and analyzed in detail. It is shown that in aqueous solution the formyl hydrogen abstraction is energetically favored. The results confirm the validity of the hypothesis that the electrochemical incineration of formic acid may occur in solution according to the outer sphere mechanism, without adsorption of intermediates.